Physicians' perception of childhood asthma in Turkey: more appropriate practice among female physicians - Sekerel Bulent E; Civelek Ersoy; Soyer Ozge (BMC, 2008)
Abstract Background Low levels of asthma control worldwide point to the possibility of sub-optimal management; therefore, documentation of physicians' perception is critical for future interventions. Our aim was to examine self-reported management abilities of Turkish physicians dealing with children with asthma, document the factors affecting appropriate decisions and compare the results with those of a previous survey. Methods Physicians were surveyed via a questionnaire aimed to document self-perceived asthma knowledge and attitudes in asthma management. Results The majority of physicians were male (63%) and examined 234 ± 9 patients per week. Infrequent use of objective parameters in asthma diagnosis and attack severity assessment was reported and most preferred nebulized corticosteroids to the systemic form in acute asthma. Even though self-perceived overall asthma knowledge did not differ between genders (p = 0.098), male physicians scored higher than females for inhaled steroids for acute asthma (2.8 ± 0.12 vs 2.17 ± 0.2, respectively, p = 0.007), while female physicians recorded more frequent use of inhaled steroids for chronic asthma (3.72 ± 0.08 vs 3.43 ± 0.07, respectively, p = 0.006). Female physicians' scoring for "symptom control" as the main aim of asthma management was higher than that of their male counterparts (3.88 ± 0.04 vs 3.65 ± 0.06, respectively, p = 0.002). Conclusion Although there were some discrepancies between guidelines and clinical practice, most applications of Turkish physicians dealing with children with asthma were appropriate. Interestingly, when scores of female versus male physicians were compared, it can be suggested that female physicians have a more appropriate perception of asthma, indicating a significant contribution of gender-related factors in clinical attitudes and beliefs.